Development of Student Need-Based Library Facilities to Support Effective Learning - Eritrina Eritrina (Journal of Educational Development and Learning (JEDAL), 2025)
Academic libraries play a strategic role in supporting learning processes through the provision of learning resources, academic facilities, and information services that meet students’ needs. Technological advancements and changes in student learning patterns require libraries to continuously improve their facilities to create effective and adaptive learning environments. This study aimed to analyze students’ needs regarding library facilities as a basis for developing facilities that support effective learning at Universitas Negeri Makassar. A quantitative approach with a descriptive research design was employed. The population consisted of all students of Universitas Negeri Makassar, while the sample comprised 100 students selected through purposive sampling. Data were collected using a questionnaire distributed to students who were actively utilizing library facilities during the research period. The data were analyzed using descriptive statistics, including frequencies, percentages, and mean scores. The findings revealed that all library facility indicators were rated in the high to very high categories. Library Layout obtained the highest mean score (4.28), followed by Book Collections (4.25), Internet Access (4.24), Space Capacity (4.22), and Technological Facilities (4.11). These results indicate that the library facilities generally meet students’ needs and contribute to effective learning. Nevertheless, the development of technological facilities should be prioritized to enhance library services and respond more effectively to the growing demands of digital learning. This study recommends strengthening technological infrastructure, expanding access to electronic information resources, and conducting regular evaluations of user needs as a foundation for sustainable library facility development.